Older Adult Stair and Walking Speeds from Controlled Trials as Inputs into Simulations of Retirement Home Evacuation - Forrest, Bronwyn; Van Ooteghem, Karen; Jones, Bryn; Gales, John; Weckman, Elizabeth (Collective Dynamics, 2024)
This work aims to add to the current database of human movement data, specifically, 3-stair descent speeds from controlled trials of typically aging older adults (n=212, aged 60-99) with and without mobility impairments. Additionally, to explore the impacts of model input parameters, stair and walking speeds obtained from controlled trials are used to simulate first-iteration Canadian retirement home egress scenarios with Pathfinder. Analysis of descending stair speeds reveal interesting trends and key inter-population variations. Moreover, when the stair and horizontal walking speeds determined from these controlled trials are used as inputs into the illustrative egress simulations, a difference in predicted egress outcomes are seen compared to when model defaults are used. Together, the findings indicate important egress considerations for a vulnerable population.